Match physical performance profiles in professional football: a comparative analysis among players` positions in the European five top leagues - Castellano, J.; Huarte, X.; Casamichana, D. (International Journal of Performance Analysis in Sport, 2025)
The aim of this study was to profile the physical-performance related match-data of players (n = 3211) in five leagues (Bundesliga: BU, Ligue1: L1, La-Liga: LL, Premier-League: PL, and Serie-A: SA), regarding five positions: central-defender (CD), fullback (FB), central-midfielder (CM), winger (WN), and forward (FW). The physical-variables were: total-distance (TD), distance at 15-20 km·h-1 (RUNd), distance and efforts at 20-25 km·h-1 (nHSR, HSRd) and > 25 km·h-1 (nSPR, SPRd), accelerations at 1.5-3.0 m·s-2 (mACC), and > 3.0 m·s-2 (hACC), decelerations at -1.5/-3.0 m·s-2 (mDEC), and <-3 m·s-2 (hDEC), and peak-velocity (VMAX). Principal-Component (PC), Cluster and a Mixed-Model analysis were implemented. Results: 1) two PC (explained variance > 75%) grouped variables related to the amount of activity (PC1 = TD, RUNd, nHSR, HSRd,m ACC and mDEC) and intensity (PC2 = nSPR, SPRd, VMAX, hACC and hDEC); 2) CD and CM, in any league, were mainly grouped in clusters 1 and 4, respectively, while the rest FB, FW and WN, were distributed in clusters 3 and 5; 3) the SA and PL leagues, the FW, FB and WN positions and clusters 4 and 5 were profiles closest to the intensity. Knowing physical profiles could be useful both for the recruitment department of the club and for the analysts in those teams that take part in international competitions.